Frontispiece: Phosphoric‐Acid Retention in High‐Temperature Proton‐Exchange Membranes. Issue 70 (16th December 2022) - Tang, Hongying; Gao, Jian; Wang, Yidong; Li, Nanwen; Geng, Kang
Abstract : There are mainly four strategies to mitigate phosphoric‐acid loss for high‐temperature proton‐exchange membranes: (1) Chemical modification of polymer mainchains with phosphonic acid groups; (2) Introduction of stronger interaction by construction of quaternary ammonium‐biphosphate ion pairs in the membranes; (3) Capillary siphoning effect provided by polymers with intrinsic micropores; (4) Doping of inorganic particles in the polymer matrix. For more information, see the Concept article by H. Tang, N. Li, K. Geng and co‐workers (DOI: 10.1002/chem.202202064 ).